Effect of NPK Fertilizer Dosage and Plant Spacing on Growth and Yield of Cauliflower (Brassica oleraceae L.) - Jadidah, Riskon; Febria, Dila; Rahhutami, Ratih; Darma, Wika Anrya (Politeknik Negeri Lampung, 2024)
Cauliflower is a vegetable with high economic value. However cauliflower production was decrease caused by crop failure resulting, pest and deseasse attack. Decrease of Cauliflower production related to soil fertility. One of attempts to overcome this problem is combining NPK fertilizer and setting of plant spacing to increase cauliflower production in Indonesia. The aims of this research is Firts: Determine the most effective dose of NPK fertilizer for growth and yield cauliflower, Seccond: Finding the optimal plant spacing to support growth and yield of cauliflower, and Third: indentifying best combinations of NPK fertilizer dosage and plant spacing to increasing growth and yield of cauliflower production. This research used a factorial Randomized Group Design (RAK) by two factors: NPK fertilizer dose (0 g/plot, 5 g/plot, 10 g/plot dan 15 g/plot), plant spacing (40 x 45 cm, 50 x 45 cm, and 60 x45 cm). Results of this research show that aplication doses of NPK fertilizer provides best results at an NPK fertilizer dose of 10 g/plot. Application of plant spacing did not show significant differences throughout observed of all parameters. Additionally, no interactions from combination of NPK fertilizer dosage and plant spacing cauliflower.